(untitled) (E Conference Zone, 2022)
The article presents in detail the history of the emergence and development of the term "intertextuality", as well as the history of the phenomenon described by this term before it began to be designated by this word. The features of the understanding of intertextuality by various scientific schools, the narrow and broad interpretation of the term are analysed.